Ecological patterns of Tuber melanosporum and different Quercus Mediterranean forests: Quantitative production of truffles, burn sizes and soil studies - Garcia-Montero, Luis G.; Manjon, Jose L.; Pascual, Cristina; García-Abril, Antonio (Forest Ecology and Management, 2007)
Most studies on Tuber melanosporum fail to supply statistical data on carpophore production and other quantitative data associated with trufﬂe ecology, such as the development of its burns (trufﬂe production sites). During 7 years, we studied 208 burns associated with Quercus ilex subsp. ballota, Q. faginea, Corylus avellana and Tilia platyphyllos in the centre of the Iberian Peninsula. The results showed that burn size is a very signiﬁcant factor as it accounts for 38% of the variance in carpophore production. However, no signiﬁcant difference in the size of burns was observed between ﬁve types of wood, although signiﬁcant variability in carpophore production existed between these wood types. Furthermore, statistical analysis shows that a high concentration of active carbonate in the soil accounts for up to 51% of the variance in T. melanosporum burn size. The ecological conditions of burns cause elevated concentrations of active carbonate and exchangeable Ca 2+ , and T. melanosporum activity and burn size are simultaneously favoured by a high concentration of both factors, which suggests a feedback process. These results may indicate a possible application for the use of calcareous amendments in natural burns and trufﬂe cultivation. Moreover, we also determined the considerable trufﬂe-producing ability and mycorrhizing capacity of Quercus faginea. Although Q. faginea is a very little-known species in trufﬂe culture, the results provide support for its implementation
Keywords: active carbonate; Quercus faginea; truffle burn; truffle production; truffle soil; Tuber melanosporum

Ecological patterns of Tuber melanosporum and different Quercus Mediterranean forests: Quantitative production of truffles, burn sizes and soil studies - Garcia-Montero, Luis G.; Manjon, Jose L.; Pascual, Cristina; García-Abril, Antonio (Forest Ecology and Management, 2007)
Most studies on Tuber melanosporum fail to supply statistical data on carpophore production and other quantitative data associated with trufﬂe ecology, such as the development of its burns (trufﬂe production sites). During 7 years, we studied 208 burns associated with Quercus ilex subsp. ballota, Q. faginea, Corylus avellana and Tilia platyphyllos in the centre of the Iberian Peninsula. The results showed that burn size is a very signiﬁcant factor as it accounts for 38% of the variance in carpophore production. However, no signiﬁcant difference in the size of burns was observed between ﬁve types of wood, although signiﬁcant variability in carpophore production existed between these wood types. Furthermore, statistical analysis shows that a high concentration of active carbonate in the soil accounts for up to 51% of the variance in T. melanosporum burn size. The ecological conditions of burns cause elevated concentrations of active carbonate and exchangeable Ca 2+ , and T. melanosporum activity and burn size are simultaneously favoured by a high concentration of both factors, which suggests a feedback process. These results may indicate a possible application for the use of calcareous amendments in natural burns and trufﬂe cultivation. Moreover, we also determined the considerable trufﬂe-producing ability and mycorrhizing capacity of Quercus faginea. Although Q. faginea is a very little-known species in trufﬂe culture, the results provide support for its implementation
Keywords: active carbonate; Quercus faginea; truffle burn; truffle production; truffle soil; Tuber melanosporum